( f + g ) (x) = –2x + 6
( f – g ) (x) = 8x – 2
( f × g ) (x) = –15x2 + 2x + 8
<span>\mathbf{\color{purple}{ \left(\small{\dfrac{\mathit{f}}{\mathit{g}}}\right)(\mathit{x}) = \small{\dfrac{3\mathit{x} + 2}{4 - 5\mathit{x}}} }}<span><span>(<span><span>g</span><span>f</span><span></span></span>)</span>(x)=<span><span><span>4−5x</span></span><span><span>3x+2</span></span><span></span></span></span></span>
Answer:
v = 27
Step-by-step explanation:
20 = v + 9 - 16
20 = v + (9 - 16)
20 = v - 7
v = 27
We must follow order of operations rules (PEMDAS) here: exponentiation first, followed by multiplication and division, followed by addition and subtraction.
Thus, -2^2-3(-2)+1 becomes:
-[4] + 6 + 1 = 2 + 1 = 3 (answer)